Walter: A story of resilience and hope - Indrani Naidoo (UN Chronicle, 2014)
The name Walter is taken from a Germanic name meaning ruler of the army (http:/www.behindthename.com), yet the Walter I was honoured to meet and connect with, like a mother to a son, is a beautifully made gentle soul, soft spoken, always smiling and showing no outer scars of a person exposed to some of the worst brutalities against humankind. On the contrary, he is poised, warm, friendly and grateful for his portion, for his cup in life, once empty even of basic needs that every child is entitled to and flung to the harsh elements of fate, is brimming with goodness and soon will overflow. This is because a young man realized that if he was so cruelly flung into the valley of death as a child, alone, confused, hungry, thirsty and lost in the crowds of hurting people fleeing for their lives with empty hands and aching hearts, he was alive for a purpose. All they had was the sky above as their roof and each otherstrangers by blood but brothers in circumstances. He remains beautifully made and hopeful that there is still goodness to be enjoyed.